2022
DOI: 10.1002/mgg3.2083
|View full text |Cite
|
Sign up to set email alerts
|

A novel splicing variant of VCAN identified in a Chinese family initially diagnosed with familial exudative vitreoretinopathy

Abstract: Background Wagner vitreoretinopathy (WVR) is a rare autosomal dominant vitreoretinopathy caused by pathogenic variants in the VCAN gene. The aim of this study was to report a novel splicing variant in VCAN identified in a three‐generation Chinese family initially diagnosed with familial exudative vitreoretinopathy and to describe the patients' clinical features. Methods Four affected individuals from a three‐generati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(64 reference statements)
0
1
0
Order By: Relevance
“…It has been previously reported that VCAN variant can lead to Wagner syndrome, which is often comorbid with anterior segment dysplasia, and the diagnosis is founded on the presence of characteristic ocular manifestations and family history consistent with autosomal dominant inheritance. In 2021, Zhong et al [42] , reported the discovery of a novel splice variant of the VCAN in a Chinese family diagnosed with familial exudative vitreoretinopathy, with vitreous syneresis and binocular retinal detachment at different ages in all 4 patients. In our study, family 2 patient in this study had typical fundus changes of FEVR such as vascular rigidity and increased branching of peripheral retinal vessels, but no obvious complaints of anterior segment dysplasia and night blindness, in combination with the literature, led to the nal diagnosis of FEVR in family 2.…”
Section: Discussionmentioning
confidence: 99%
“…It has been previously reported that VCAN variant can lead to Wagner syndrome, which is often comorbid with anterior segment dysplasia, and the diagnosis is founded on the presence of characteristic ocular manifestations and family history consistent with autosomal dominant inheritance. In 2021, Zhong et al [42] , reported the discovery of a novel splice variant of the VCAN in a Chinese family diagnosed with familial exudative vitreoretinopathy, with vitreous syneresis and binocular retinal detachment at different ages in all 4 patients. In our study, family 2 patient in this study had typical fundus changes of FEVR such as vascular rigidity and increased branching of peripheral retinal vessels, but no obvious complaints of anterior segment dysplasia and night blindness, in combination with the literature, led to the nal diagnosis of FEVR in family 2.…”
Section: Discussionmentioning
confidence: 99%